Metabolic and biochemical profile in women with polycystic ovarian syndrome attending tertiary care centre of central NEPAL - Isha Rajbanshi; Vijay Kumar Sharma; Eans Tara Tuladhar; Aseem Bhattarai; Mithileshwar Raut; Raju Kumar Dubey; Poonam Koirala; Apeksha Niraula (BMC, 2023)
Abstract Background Polycystic Ovarian Syndrome (PCOS) is a common endocrinopathy in women of reproductive age group and is highly associated with an increased risk of diabetes, hypertension, cardiovascular disease, and hyper estrogen-related malignancies in women with PCOS. This study was intended to assess the metabolic and hormonal profile of the patients with polycystic ovarian syndrome attending a tertiary care hospital. Methodology A descriptive cross-sectional study was conducted among 107 women diagnosed with polycystic ovarian syndrome from the Department of Clinical Biochemistry of Tribhuvan University and Teaching Hospital. Descriptive analysis was performed to determine the socio-demographic characteristics of the participants. Bivariate analysis was conducted to determine using a t-test for comparing means between two groups and ANOVA for comparing the hormonal and metabolic parameters. Results The mean age of the participants was 27 ± 4 years. This study showed that blood pressure was significantly higher in overweight and obese women (p = 0.001). The obese group had significantly higher serum TSH than the normal group (10.04 vs. 2.73, p = 0.001). Abnormal glucose and hyperinsulinemia were present in 4% of the patients, while 40% had Vitamin D deficiency. Hypothyroidism (TSH ≥ 4.5 mIU/ml) was found in 11% of the PCOS participants with a mean value of 6.65 ± 21.17 mIU/ml. Hyperprolactinemia ≥ 26.8 ng/ml was depicted in 21% of the study population with a mean value of 37.25 ± 21.86 ng/ml. Conclusion Our study demonstrated that PCOS is most commonly prevalent in young women of the reproductive age group which can lead to reproductive, metabolic, and oncological complications in the long term. LH/ FSH ratio was found to be significantly deranged indicating that PCOS should be diagnosed and treated early in the adolescent age group.